Postoperative red blood cell transfusion and morbid outcome in uncomplicated cardiac surgery patients - Möhnle, Patrick; Snyder-Ramos, Stephanie; Miao, Yinghui; Kulier, Alexander; Böttiger, Bernd W.; Levin, Jack; Mangano, Dennis T. (Intensive care medicine, 2011)
To evaluate postoperative red blood cell (RBC) transfusion and its association with postoperative cardiac events and multiorgan morbidity in uncomplicated cardiac surgery patients.
First published online: 19 August 2010
Gesehen am 01.09.2022